Number 2 Feibi Recipe Ameliorates Pulmonary Fibrosis by Inducing Autophagy Through the GSK-3β/mTOR Pathway - Liu, Haoge; Pang, Qinglu; Cao, Fang; Liu, Zhaoheng; Wei, Wan; Li, Zhipeng; Long, Qi; Jiao, Yang (Frontiers in Pharmacology, 2022)
Number 2 Feibi Recipe (N2FBR) is a traditional Chinese medicine formula for treating idiopathic pulmonary fibrosis. N2FBR inhibits H2O2-mediated oxidative stress damage in alveolar epithelial cells by increasing autophagy, as we previously demonstrated. However, it is unknown if similar mechanisms occur in vivo. We established a pulmonary fibrosis model by instilling bleomycin (BLM) from the airway to examine the effects of N2FBR on pulmonary fibrosis and investigate its probable mechanism in this work. We discovered that N2FBR treatment effectively alleviated interstitial fibrosis as well as collagen deposition, primarily in upregulating SOD, GSH-Px, T-AOC and downregulating MDA content. N2FBR also increased the expression of LC3B, Beclin-1, LAMP1, TFEB and downregulated the expression of p62, legumain. N2FBR treatment boosted the production of autophagosomes, according to the results of the TEM observation. Furthermore, we explored that N2FBR exerted its anti-oxidative stress and pro-autophagy effects via GSK-3β/mTOR signalling pathway. Therefore, these results provide further evidence for the protective effect of N2FBR in pulmonary fibrosis. Our findings could have ramifications for the development of antifibrosis therapies.